Unconfined compressive strength characteristic of soft soil mixed with lime and nano alumina - Al-Mansob, Ramez Al-Ezzi Abduljalil; Wei, Fua Wong; Alsharef, Jamal; Jassam, Taha; Jing, Lin Ng; Ali, Shaban; Yusof, Zeety; , (American Institute of Physics Inc., 2021)
Soil is one of the common materials used in construction industry whether it is for groundwork, infrastructure or as building materials. However, construction issues arise when structures are built on soft soil such as soft clay that causes instability and settlement. In order to improve the soil strength, various methods had been adopted by researchers such as the use of stabilizers like lime, cement and fly ash. This paper presents the improvement of native clay soil stability by mixing the soil with nano alumina and the lime. Part of the reason of using the nano alumina is that the nanomaterial nowadays has become one of the popular materials in the research study which lead to possible application in the geotechnical field. To examine the effect of nano alumina and the lime on the soil stability, unconfined compression strength test was adopted. In this study, 0 % and 5 % of lime content was used to examine the effect of lime on the native clay soil while the percentage of nano alumina used to study the effect of nanomaterial was 0.05 %, 0.1 % and 0.2 %. In the end, the results showed that the addition of lime and nano alumina does improve the compression strength of the clay soil.